A sufficient condition for graphs to have id-hamiltonian [a, b]-factors - Zhou, Sizhong; Zhang, Tao; Xu, Lan (Utilitas Mathematica, 2019)
Let a,b be two integers such that 2 ≤ a < b. An [a, 6]-factor is Hamiltonian if it includes a Hamiltonian cycle. We say that a graph G contains an ID-Hamiltonian [a, b-factor if G-X has a Hamilto-nian [a, 6]-factor for every independent set X of a graph G. In this paper, we obtain an independence number and connectivity condition for graphs having ID-Hamiltonian [a,b]-factors. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.